2019
DOI: 10.1590/s1678-3921.pab2019.v54.01003
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic biofortification of common bean grain with zinc

Abstract: The objective of this work was to evaluate the effects of the split and combinated application of foliar zinc (ZnF) + soil Zn (ZnS) on Zn concentration in the grains (ZnCG) of common bean (Phaseolus vulgaris). Two experiments were carried out in a greenhouse during two seasons. In the first experiment, two common bean cultivars received six ZnF rates (0, 120, 240, 480, 720, or 1,200 g ha-1), with split applications at the R5, R7, and R8, or R7 and R8, or R8 plant stages. In the second experiment, one cultivar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Studies determining the impact of applying Zn from 0 to 10 kg ha −1 have demonstrated the potentially improved nutritional quality of bean grains, without toxicity symptoms, in tropical soil [71]. The sole application of Zn may lead to a negative relation with Zn use efficiencies [72]; however, inoculant strains of Bacillus sp. and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies determining the impact of applying Zn from 0 to 10 kg ha −1 have demonstrated the potentially improved nutritional quality of bean grains, without toxicity symptoms, in tropical soil [71]. The sole application of Zn may lead to a negative relation with Zn use efficiencies [72]; however, inoculant strains of Bacillus sp. and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Agronomic biofortification of soybean through soil application and foliar application at vegetative growth stage 4 (V4) and 8 (V8), and at reproductive growth stage 4 (R4) exhibited significant enhancement of Zn when it was applied at stage R4 (de Oliveira et al, 2019). In Brazil, 100% enhancement in Zn content was observed for common bean when it was treated with ZnSO 4 (5 kg Zn/ha) as soil fertilizer along with Zn at 7.8 kg/ha as foliar (Cambraia et al, 2019). A recent study has reviewed the conventional strategies for combating the problem of Zn deficiency and throws light on modern genetic technologies to fortify common beans to fight against Zn deficiency (Philipo et al, 2021).…”
Section: Strategies For Addressing Zn Deficiencymentioning
confidence: 99%
“…Germination caused drastic increase in the Zn content. Zn is predominantly present in the cotyledon of legumes (53) and tends to interact with proteins as well as other macromolecules and reduce its extractability (54). Germination causes modification of cellular structure of the grain by virtue of development of micro cracks and fissures and weakens the bond of Zn with other macromolecules with their consequent better extractability (38).…”
Section: Macro and Micro Mineralsmentioning
confidence: 99%